Penentuan Protein Antigen Limfosit Sapi yang Berasal dari Sapi Bali dan Sapi Peranakan Ongole (DETERMINATION OF THE PROTEIN OF BOVINE LYMPHOCYTE ANTIGEN, OF BALI CATTLE AND ONGOLE CROSS BREED CATTLE) - Suwiti, Ni Ketut; Rantam, Fedik Abdul (Jurnal Veteriner; Vol 4 No 2 (2003), 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: Bovine lymphocyte antigen (BoLA), bali cattle, ongole cross breed cattle